Cover Jurnal Fitopatologi Vol. 18 No. 1, Januari 2022 - Hidayat, Sri Hendrastuti (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2022)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology Vol. 18 No. 1, Januari 2022